Talking the walk & walking the talk : a rhetoric of rhythm - Shell, Marc (Verbal arts--studies in poetics., 2015)
"This book argues that we should regard walking and talking in a single rhythmic vision. In doing so, it contributes to the theory of prosody, our understanding of respiration and looking, and, in sum, to the particular links, across the board, between the human characteristics of bipedal walking and meaningful talk. The author first introduces the philosophical, neurological, anthropological, and aesthetic aspects of the subject in historical perspective, then focuses on rhetoric and introduces a tension between the small and large issues of rhythm. He thereupon turns his attention to the roles of breathing in poetry--as a life-and-death matter, with attention to beats and walking poems. This opens onto technical concepts from the classical traditions of rhetoric and philology. Turning to the relationship between prosody and motion, he considers both animals and human beings as both ostensibly able-bodied creatures and presumptively disabled ones. Finally, he looks at dancing and writing as aspects of walking and talking, with special attention to motion in Arabic and Chinese calligraphy. The final chapters of the book provide a series of interrelated representative case studies"--